Expression profiles of long noncoding RNAs in human corneal epithelial cells exposed to fine particulate matter. (January 2022) - Song, Fan; Chen, Zhijian; Lyu, Danni; Gu, Yuzhou; Lu, Bing; Hao, Shengjie; Xu, Yili; Jin, Xiuming; Fu, Qiuli; Yao, Ke
Abstract: Purpose: The aim of this study was to investigate the expression profiles of long noncoding RNAs (lncRNAs) in human corneal epithelial cells (HCECs) exposed to fine particulate matter (PM2.5 ) and to identify potential biological pathways involved in PM2.5 -induced toxicity in HCECs. Methods: Using RNA sequencing (RNA-seq) and hierarchy clustering analysis, lncRNA expression profiles in PM2.5 -treated and untreated HCECs were examined. Gene ontology (GO) enrichment analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis were performed to predict the role of altered lncRNAs in biological processes and pathways. A quantitative real-time reverse transcription polymerase chain reaction (qRT-PCR) assay was conducted to verify the RNA-seq results in HCECs and human corneal epithelial cell sheets. Results: In total, 65 lncRNAs were altered in the PM2.5 -treated HCECs, including 41 upregulated and 24 downregulated lncRNAs. The results of the qRT-PCR assay were consistent with those of the RNA-seq analysis. The expression of two significantly upregulated lncRNAs was confirmed in human corneal epithelial cell sheets. The GO analysis demonstrated that altered lncRNAs in the PM2.5 -treated HCECs were significantly enriched in three domains: cellular component, molecular function, and biological process. The KEGG pathway analysis revealed enriched pathways of lncRNA co-expressed mRNAs, including cancer, RNA transport, and Rap1 signaling. Conclusions: Our results suggest that lncRNAs are involved in the pathogenesis of PM2.5 -induced ocular diseases, exerting their effects through biological processes and pathogenic pathways. Among the altered lncRNAs, RP3-406P24.3 and RP11-285E9.5 may play significant roles in PM2.5 -induced ocular surface injury. Highlights: Comparison of the lncRNA expression profiles of the PM2.5-treated and untreated HCECs. The KEGG pathway analysis revealed enriched pathways of lncRNA co-expressed mRNAs. The results of the qRT-PCR test revealed increased expression of RP11-285E9.5 and RP3-406P24.3.